Microbial Diversity in Soil under Different Land Use Systems in Sub-Mountainous Zone of Punjab - and V. Sharma, S. Garcha, P. Katyal (Journal of the Indian Society of Soil Science, 2016)
The surface soil samples (0-15 cm) were collected from different land use systems at AICRP on Dryland Agriculture Center of Punjab Agricultural University, Ballowal Saunkhri, district SBS Nagar, Punjab and analyzed for soil physicochemical and microbial diversity. The soils were neutral to saline in reaction and low to medium in organic carbon content. Soil EC ranged between 0.23 and 0.31 dS m-1. Available nitrogen, phosphorus and potassium in soil varied from 176-376, 15-60 and 90-232 kg ha-1, respectively. Wide variation in the soil microbial population was recorded under different land use systems. The bacterial, fungal and actinomycetes population varied from 6.8×103 to 1.4×105 cfu g-1, 2.9×10 to 3.6×104 and 2.0×103 to 5.3 × 104, respectively under different land use systems. Total microbial population was maximum in the mixed forest followed by shesham plantation and kinnow orchards and least in the fodder crop (napier hybrid bajra) and cultivated area (maize-wheat). Non-significant correlation of soil properties with microbial diversity was recorded due to the low moisture content in soil samples under rainfed conditions.